Sustaining the shelf life of fresh food in cold chain – A burden on the environment - Oludaisi Adekomaya; Tamba Jamiru; Rotimi Sadiku; Zhongjie Huan (Alexandria Engineering Journal, 2016)
Energy consumption in cold chains has been predicted to rise significantly in view of the increasing world population. Of critical attention is the increasing number of road transport refrigeration which is highly gaining enormous ground globally. In view of the fact that 40% of all foods require refrigeration, 15% of world fossil fuel energy is used in food transport refrigeration. This concern necessitates this study to examine cold chain system with the emphasis on the impact of energy consumption in sustaining the shelf life of fresh food. As the world continues to battle with the global warming occasioned by emission of carbon dioxide from fossil fuel, this study identifies alternative means of saving energy in food transportation system through minimizing energy consumption in diesel engine driven vapour compression system. Preserving perishable fresh food (mainly vegetable) under sub-zero weather is another debacle the authors envisaged in the quest to reduce fossil fuel consumption. This process requires heating the mechanical refrigeration unit in a reverse-cycle to raise the temperature at 0 °C which may further result in more energy demand. The conclusion drawn from this study could be useful in re-designing food transport system for optimal energy saving.